1996
DOI: 10.1083/jcb.134.5.1109
|View full text |Cite
|
Sign up to set email alerts
|

Centromere and telomere movements during early meiotic prophase of mouse and man are associated with the onset of chromosome pairing.

Abstract: Abstract. The preconditions and early steps of meiotic chromosome pairing were studied by fluorescence in situ hybridization (FISH) with chromosome-specific DNA probes to mouse and human testis tissue sections. Premeiotic pairing of homologous chromosomes was not detected in spermatogonia of the two species. FISH with centromere-and telomere-specific DNA probes in combination with immunostaining (IS) of synaptonereal complex (SC) proteins to testis sections of prepuberal mice at days 4-12 post partum was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
406
3
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(443 citation statements)
references
References 90 publications
32
406
3
2
Order By: Relevance
“…SC formation initiates during the leptotene stage. The expression of a structural component of the SC, Sycp3, appeared as aggregates of this protein in the preleptotene nucleus, as previously described in both zebrafish (Ozaki et al, 2011) and mice (Scherthan et al, 1996). However, there was no development of cells that have the SC structure in the its mutant and the responsible gene may, therefore, be involved in the initiation of SC formation in the leptotene stage.…”
Section: A Mutation Affecting the Onset Of Meiosis In Zebrafish Spermsupporting
confidence: 64%
See 1 more Smart Citation
“…SC formation initiates during the leptotene stage. The expression of a structural component of the SC, Sycp3, appeared as aggregates of this protein in the preleptotene nucleus, as previously described in both zebrafish (Ozaki et al, 2011) and mice (Scherthan et al, 1996). However, there was no development of cells that have the SC structure in the its mutant and the responsible gene may, therefore, be involved in the initiation of SC formation in the leptotene stage.…”
Section: A Mutation Affecting the Onset Of Meiosis In Zebrafish Spermsupporting
confidence: 64%
“…The expression of Sycp3 commenced in preleptotene spermatocytes, identified by the presence of one or more intranuclear Sycp3 aggregates (Fig. 5A), which have been shown to mark the onset of prophase I in male germ cells in mouse and cow (Scherthan et al, 1996;Pfeifer et al, 2001). In zebrafish spermatocytes at the leptotene stage, the Sycp3 signals were detectable as short fine threads, starting from one side of the nucleus with a distinct polarity (Fig.…”
Section: Spermatocytes From Mutant Testes Fail To Progress Beyond Promentioning
confidence: 93%
“…2A). These results are consistent with the previous observations (Scherthan et al 1996) but partly contradictory to a recent study that reports the appearance of a transient pairing peak at late premeiotic S phase (see the Discussion; Boateng et al 2013). Under our experimental conditions, the distance between paired FISH signals decreases to <1.35 mm in 45%;60% of zygotene spermatocytes and in >95% of pachytene spermatocytes (Fig.…”
Section: Homolog Pairing Initiates In Early Leptotenecontrasting
confidence: 47%
“…The telomeres move and cluster in the nuclear membrane close to the cytoplasmic centriole during the transition of leptotene to zygotene (zygos, greek paired). This very transient conformation is called bouquet stage and it is suggested that the telomere clustering supports the homology search and the alignment of the homologs as it coincides with synapsis initiation in many species (Scherthan et al 1996). Synapsis is characterized by the assembly of the central region of the SC.…”
mentioning
confidence: 93%